Enhancing the barrier height for Yb(iii) single-ion magnets by modulating axial ligand fields. Issue 79 (4th September 2020) - Borah, Aditya; Dey, Sourav; Gupta, Sandeep K.; Walawalkar, Mrinalini G.; Rajaraman, Gopalan; Murugavel, Ramaswamy
Abstract : Progressive weakening of the axial ligand field, by keeping the equatorial field constant, enhances the barrier height for magnetic reversal in six-coordinate pseudo-octahedral Yb(iiii ) single ion magnets. Abstract : The effect of systematic modification of the axial ligand field X on U eff values in Yb(iii )-based SIMs, [Yb(Ph3 PO)4 X2 ]X′ (X, X′ = NO3 (1 ), OTf (2 ) and X = I/Br/Cl; X′ = I3 (3 )), whose equatorial Ph3 PO ligation remains unchanged, has been investigated. Combined magnetic studies coupled with ab initio calculations reveal weakening of the axial ligand fields leading to the increase in the energy barrier, apart from suggesting the operation of different relaxation pathways.